Expert System Application for Diagnosis of Engine Damage of 4- Clutch Motor - Dira Suprima (Jurnal Sistem Informasi, 2010)
In scientific writing, the author discusses the development of Expert System,which is one field of artificial intelligence techniques in the computer field. Herethe author uses the method of production functions that included rules inpredicate calculus as a way of knowledge representation is applied in TurboProlog programming language, where the application is used to look for damagethat may occur in 4-stroke motorcycle engine in accordance with existing traits.Turbo Prolog programming language is a form of declarative programminglanguage developed in the early 1970s by Alain Colmerauer from the Universityof Marseilles in France.Expert Systems with Applications made to Diagnose Damage Motor 4-strokeengine is expected to develop existing theory base significantly, so that thelearning is more easily understood with the success of this Expert Systemapplications and can help users who do not know the motor in detail about themotor 4 - not to get consideration before taking further action if there is damageto their motor.